Fear of Missing Out (FOMO) Pada Mahasiswa Pengguna Media Sosial: Bagaimana Korelasi Dengan Kecerdasan Emosional? - Mardhiyah, Zahrina; Maghfirah, Anggia (ANIMA Indonesian Psychological Journal, 2025)
The high use of social media among university students tends to have a negative impact on the individual's psychological condition. One of them is the fear of missing out (FOMO), which is a feeling of fear of being left behind in information and events that encourages the formation of negative feelings and behavior. Protective factors are needed so that the level of fear of missing out (FOMO) does not increase, and one of them is emotional intelligence. However, there has been no correlational study between emotional intelligence and fear of missing out (FOMO) in Indonesia. Therefore, this study aims to identify the relationship between emotional intelligence and fear of missing out (FOMO) in university student social media users, with a quantitative correlational approach on study participants who are: (1) university students; (2) aged 18-24 years; and (3) using at least one social media. A total of 220 study participants were obtained by convenience sampling. Data collection was carried out using the Online Fear of Missing Out Inventory (ON-FOMO; 20 items; α = .792) and Alat Ukur Kecerdasan Emosional Tarumanagara (Tarumanagara Emotional Intelligence Measurement Inventory; 28 items; α = .893). The study data were analyzed using Pearson’s Product Moment, and the results showed that there was a negative correlation between emotional intelligence and fear of missing out (FOMO; rxy = - .480 > rtable; p = .000 < .05), with the strength of the relationship in the Medium category. These results mean that the higher the emotional intelligence, the lower the level of fear of missing out (FOMO), and vice versa. In addition, the results of this study show that emotional intelligence influences fear of missing out (FOMO) by 23%, with the remaining 77% contribution influenced by other factors not discussed in this study.